Effects of structural distortion on the optoelectronic properties and reactivity of fullerenes: a DFT study - Cachaneski-Lopes, Joao P. [UNESP] (2021)
Fullerene is a compound made up solely of carbon atoms structured in the form of cages with high symmetry. These compounds present a variety of applications, mainly due to their unique mechanical and electronic properties. In general, there is a relative scarcity of studies on the effect of mechanical deformations on the electronic properties of fullerenes, although some studies suggest the plausibility of such structural changes in specific situations. In the present report, density functional theory-based calculations were employed to evaluate the effects of structural deformations in the electronic, optical and reactivity properties of C-60 and PCBM. The results evidence the existence of distinct regimes of the structural changes, which influence the intrinsic properties of these compounds in a distinct manner. In particular, it was observed that the compression/stretching of the structures can lead to the narrowing of the electronic gaps, enhanced optical absorption, decreased mobility of the holes, and changes in local reactivities. This information can help the interpretation of electronic processes and specific reactions of single molecules subjected to high pressures. Graphic abstract